Analisis Fatwa ‘Ali Jum'ah tentang Nikah ‘Urfi dalam Kitab al-Kalim al-Thayyib Fatawa Ashriyyah - Ulya Hikmah Sitorus Pane; Muhammad Rozali (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2016)
This study aims to analyze fatwa ˜'Ali Jum'ah, a Grand Mufti of Egypt about 'Urfi Marriage in al-Kalim at-Thayyib Fatawa Ashriyyah. This study used a qualitative descriptive approach, and the type of research literature (Library Research). This research was conducted by examining the writings to solve a problem with a critical and in-depth manner. The findings of this study are: First, 'Urfi Marriage is a marriage that all the pillars and conditions, just not recorded in the institution of marriage registration. Second, 'Urfi Marriage is complete terms and pillars, marriage is valid and has been validated by the fatwa institution Dar al-Ifta' Egypt, through a fatwa '˜Ali Jum'ah, The fatwa was issued due to rampant 'Urfi Marriage and the high cost of the wedding, with this fatwa 'Urfi Marriage be legal. Third, the scholars differ on this marriage law, the classical scholars allowing this marriage, because the problem does not exist at the time of registration before, while contemporary scholars there are disagreements, partly justified and partly forbidden to see the conditions that developed at this.